Sprawozdanie z VI Salonu Mediacji oraz III ADR Study Space, Poznań, 13–14 maja 2019 r. - Mucha, Joanna; Tomaszewska, Paulina (Studia Prawa Publicznego, 2019)
Sprawozdanie z VI Salonu Mediacji oraz III ADR Study Space, Poznań, 13–14 maja 2019 r.